2000
DOI: 10.1128/jb.182.14.4022-4027.2000
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization of Chimeric oriT Plasmids by F and R100-1: Role of Relaxosome Formation in Defining Plasmid Specificity

Abstract: Cleavage at the F plasmid nic site within the origin of transfer (oriT) requires the F-encoded proteins TraY and TraI and the host-encoded protein integration host factor in vitro. We confirm that F TraY, but not F TraM, is required for cleavage at nic in vivo. Chimeric plasmids were constructed which contained either the entire F or R100-1 oriT regions or various combinations of nic, TraY, and TraM binding sites, in addition to the traM gene. The efficiency of cleavage at nic and the frequency of mobilization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 52 publications
2
32
0
Order By: Relevance
“…In vivo plasmid nicking and transfer experiments have demonstrated that TraI proteins from F and R100 can distinguish the two-base difference between their cognate TraI binding site (Fig. 1) and the site from the other plasmid (20,24,26,28). To quantify the binding differences, an expression construct for the R100 TraI relaxase domain (TraI36) was generated, the protein was purified, and its ssDNA binding was compared with that of the previously generated F TraI36 (27).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In vivo plasmid nicking and transfer experiments have demonstrated that TraI proteins from F and R100 can distinguish the two-base difference between their cognate TraI binding site (Fig. 1) and the site from the other plasmid (20,24,26,28). To quantify the binding differences, an expression construct for the R100 TraI relaxase domain (TraI36) was generated, the protein was purified, and its ssDNA binding was compared with that of the previously generated F TraI36 (27).…”
Section: Resultsmentioning
confidence: 99%
“…The ssDNA cleavage specificity results for F and R100 TraI36 are consistent with the results of in vivo nicking and transfer experiments using the full-length proteins. R100 TraI nicks and efficiently transfers chimeric plasmids that include the F TraI binding site (28), whereas F TraI is highly specific in its ssDNA cleavage and plasmid mobilization activities, and interacts less effectively with the R100 sequence (24, 28).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biochemical analysis of the F-plasmid proteins (16,28) and recent genetic data (11) suggest that one function of TraY is to impart stability to the complex. Further work is necessary for a detailed understanding of the activity and regulation of IncF relaxosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Using in vitro assays, TraM has been shown to interact with TraD, an inner membrane component of the transferosome encoded by the F-plasmid (1,9). TraM is essential neither for the nicking reaction that involves other components of the relaxosome nor for F-pilus assembly or mating-pair formation that involve most of the transferosome components (10,11,19,22,32). Therefore, TraM was proposed to transmit a signal between the cytoplasmic relaxosome and the transferosome during F conjugation (13,43).…”
mentioning
confidence: 99%